2014
DOI: 10.1016/j.bbadis.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

ARF tumor suppression in the nucleolus

Abstract: Since its discovery close to twenty years ago, the ARF tumor suppressor has played a pivotal role in the field of cancer biology. Elucidating ARF's basal physiological function in the cell has been the focal interest of numerous laboratories throughout the world for many years. Our current understanding of ARF is constantly evolving to include novel frameworks for conceptualizing the regulation of this critical tumor suppressor. As a result of this complexity, there is great need to broaden our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 154 publications
1
85
0
Order By: Relevance
“…These observations together suggest that p16 Ink4a and p19 Arf may play roles broader than their canonical functions in RB signaling/G 1 restriction point and p53 signaling pathways, respectively. For example, p16 Ink4a has a central role in cellular homeostasis and aging (LaPak and Burd, 2014), while p19 Arf has been shown to play important roles in metabolism and nucleolar biology (Maggi et al, 2014). The effect of Lkb1 loss on liver and spleen metastasis in the Cdkn2a/Lkb1/Braf model is notable and is consistent with the metastasis-restricting role previously attributed to Lkb1 by Liu and colleagues (2012b).…”
Section: Discussionmentioning
confidence: 99%
“…These observations together suggest that p16 Ink4a and p19 Arf may play roles broader than their canonical functions in RB signaling/G 1 restriction point and p53 signaling pathways, respectively. For example, p16 Ink4a has a central role in cellular homeostasis and aging (LaPak and Burd, 2014), while p19 Arf has been shown to play important roles in metabolism and nucleolar biology (Maggi et al, 2014). The effect of Lkb1 loss on liver and spleen metastasis in the Cdkn2a/Lkb1/Braf model is notable and is consistent with the metastasis-restricting role previously attributed to Lkb1 by Liu and colleagues (2012b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Mdm2 inhibits target DNA binding of p53 through the acidic domain in ubiquitination-independent fashion (78). Other tumor suppressors that physically interact with p53 are ARF and PML (18, 79, 80). However, these molecules are different from Dmp1 in that they bind to p53/Mdm2 and translocate p53 to the specific nuclear structure -nucleoli (81) or nuclear bodies (82) respectively to protect p53 from the negative regulation by Mdm2 while Dmp1 does not have such activity.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of Mdm2 is negatively regulated by p19 Arf (p14 ARF in humans) in response to oncogenic stress (1618). p19 Arf is an alternative reading frame gene product generated from the Ink4a/Arf locus which also encodes the cyclin-dependent kinase inhibitor p16 Ink4a .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivating mutations in PDAC involve the p16/Ink4a gene product [19][20][21]. However, p14/Arf mutations are associated with other cancer types, and the two protein products act in connected pathways-p53 signaling promotes, as necessary, cell cycle arrest, apoptosis, or senescence and is also a negative regulator of p14/Arf expression [22,23]. Studies, largescale genomic studies in particular, indicate that many important cellular pathways are deregulated in pancreatic cancer, those involving the above mentioned genes as well as others [24][25][26] and references therein.…”
Section: Pancreatic Cancer Pathwaymentioning
confidence: 99%